Relation between self diffusion and interdiffusion in Al-Cu melts - Zhang, Bo; Griesche, Axel; Meyer, Andreas (Diffusion Fundamentals, 2009)
We compare the experimental interdiffusion constants DAlCu in liquid Al81.3Cu18.7 at% to the experimental Cu self diffusion constants DCu in a similar Al80Cu20 at% melt. DAlCu are measured by an X-ray radiography technique and DCu are measured by the quasielastic neutron scattering method. It was found that DAlCu is enhanced by a factor of 3 with respect to DCu. The relation between DAlCu and DCu is investigated in the context of Darken’s equation where the interdiffusion constant DAB in a binary A-B system is approximated by a simple linear combination of the self diffusion constants DA and DB, DAB = (DAXB + DBXA)Φ (with XA and XB the mole fractions of A and B particles, respectively, and Φ the thermodynamic factor representing the thermodynamic driving force for interdiffusion). We also present a calculation of Φ from the Gibbs free energy data in molten Al-Cu. With these calculated Φ and the DCu data, interdiffusion coefficients in liquid Al-Cu have been calculated. However, the experimental DAlCu are larger than the calculated ones by a factor of 2. These results suggest that the enhancement of interdiffusion in Al-Cu liquids can not be only attributed to the thermodynamic driving force. Here we propose that the missing factor of about 2 in the Darken equation comes from the contribution of cross correlations to interdiffusion in Al-Cu liquids.